Clinical Evaluation of the Efficacy of Bovine Amniotic Fluid on Healing of Experimental Corneal Defects in Rabbits - Sağlıyan, Aydın; Çelikten, Merve; Günay, Cihan; Durmuş, Ali Said; Polat, Eren (My University, 2021)
This study was conducted to investigate the effectiveness of amniotic fluid in defects in the epithelial tissue of the cornea. In the study, 14 New Zealand rabbits, which were experimentally created with a 3 mm diameter full-thickness defect in the corneal epithelium, were used. After the rabbits were randomly divided into two groups, amniotic fluid was applied to the rabbits in the first group (AF) and saline solution was applied to the rabbits in the second group (CG) three times a day for 20 days. Clinical examinations and tests were performed on the 7th, 14th, and 20th days of the study and the condition of the corneal defects was photographed. Clinical examinations revealed that tear break-up time (TBTT), fluorescein staining, rose bengal staining, corneal turbidity, and corneal vascularization were better in the AF group than in the CG group. As a result, it is concluded that amniotic fluid is effective in corneal epithelial defects and it would be beneficial to use it in addition to medical or operative treatment.
Keywords: Treatment; epithel; amnion; cornea